Open Method of Coordination in the European research policy - Mikita, József; Nagy, János (Acta Agraria Debreceniensis, 2007)
Research, development and innovation (R+D) are of great importance nowadays as regards the competetiveness and economic growth of any given country. In the European Union the Lisbon Strategy considers R+D as a crutial means to enhance european competetiveness. The EU is substansially lagging behind its main competitors (USA, Japan) in this domain, furthermore developing countries (China, India) have recently been makinggreat progress, thus posing additional challanges to our continent.  The EU needs to assess the present situation as soon as possible and meet the latest challenges in the most efficient way. In order to achieve this objective, the concept of the European Research Area (ERA) has been elaborated with the aim of reorganising, regrouping and integrating existing structures. The open method of coordination (OMC) is playing an important role in the implementation of this common area. It constitutes an alternative policy-making merthod to pure „intergovernmentalism” and the„community method”. The OMC in the field of research policy is coordinated by the Scientific and Research Committe (CREST), which provides a forum for member states to share their experience and reach their common goals.